Alfalfa and barley association promote the ability of plant growth-promoting microbes to mitigate drought and salt stresses - Slimani, Aiman; Jemo, Martin; Oufdou, Khalid; Meddich, Abdelilah (Frontiers in Plant Science, 2025)
The advantages of crop association, or intercropping, include reducing disease cycles, suppressing weeds, and enhancing nutrient transfer between crops, both above and below-ground, are well-studied. However, the potential of associated crops to alter their physiology through interactions with rhizosphere microbes, which could mitigate drought and salt stresses, is underexplored. We investigated the impact of combining alfalfa (Medicago sativa) and barley (Hordeum vulgare) with or without plant growth-promoting microbes (PGPM) and compost on growth, physiology, stress markers, osmolytes, and antioxidant enzymes under drought and salt stress. Alfalfa and barley seedlings were grown either as sole crop or in combination, and treated with one of the biological options, including rhizobacteria (R) or mycorrhizal (M) consortia, along with compost (C) amendments, or with one of the combinations RM, RC, MC, and MRC. The seedlings were subjected to combined salt and drought stress, as well as control conditions without stress. Stress-induced markers, including malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels, osmolyte accumulation (total sugars and proteins), enzymatic antioxidant activities such as superoxide dismutase (SOD) and catalase (CAT), as well as growth, total chlorophyll, and stomatal conductance in leaf tissues, were measured at harvest. The effect of associating alfalfa and barley in the same pot resulted in highly significant effects on the shoot dry weight, H2O2, protein, MDA, and sugar contents compared to a sole cultivation of alfalfa and barley. Stressed plants showed higher levels of MDA, sugar content, and SOD activity, regardless of the crop combination. Among the biological treatments, the MRC disclosed the highest shoot dry weight, sugar content, and SOD activity for the alfalfa under crop association. Correspondence analysis with forward selection of the functional variables’ importance revealed that total chlorophyll (54.4%) and protein content (15.0%) accounted for a significant portion of the dataset’s variability. We discuss belowground biotic benefit effects of intercropping in managing abiotic stress, boosting resilience in arid systems, and promoting sustainable agricultural practices.